Harvard business review on managing external risk (Harvard Business School Pub., 2009)
It's one thing to anticipate and mitigate risks within your own company, and quite another to manage risks from events in the outside world. This collection includes advice on effective forecasting, making sound strategic decisions, and understanding how to align your strategy decisions with the financial markets.